Methods for Sensing Urban Noises - Liu, Tong; Zheng, Yu; Liu, Lubin; Liu, Yanchi; Zhu, Yanmin (2014)
Many people live in cities are suffering from noise pollution, which may impair the physical and mental health. A first step towards the understanding of urban noises is to measure real noise levels. In this technical report, we introduce two categories of methods to measure urban noise levels, discussing their advantages and disadvantages. Finally, we apply one of mobile phone-based methods to an in-the-field study that explores the noise situation in New York City (NYC) [10]. The data collected and the mobile client used in the study are available for download at [2].
MSR-TR-2014-66